Structural Evolution of Burmese Amber during Petrifaction Based on a Comparison of the Spectral Characteristics of Amber, Copal, and Rosin. (7th July 2019) - Bai, Feng; Liang, Huifang; Qu, Hongting
Abstract : This paper presents a spectroscopic analysis and solubility study of rosin, copal, and Burmese amber samples to reveal the structural changes that occur during amber formation. The infrared spectra indicate that during the long geological process of amber formation, small resin molecules first crosslinked and slowly oxidized, eventually forming a stable organic polymer mixture. An analysis of Raman peak areas demonstrated that among the tested samples, the degree of polymerization is highest in Burmese amber and lowest in rosin. Ultraviolet-visible spectra indicate the presence of unsaturated bonds (e.g., carbonyl groups) or conjugated systems in Burmese amber, copal, and rosin. The evaluation of amber, rosin, and copal solubility in six solvents (ethanol, acetone, 1, 4-dioxane, ethylacetate, N, N-dimethylamide, and dichloromethane) demonstrated that solubility decreases in the following order: rosin > copal > Burmese amber. Together, the results suggest that the structure of Burmese amber includes large organic molecules containing six-membered rings along with CH2, CH3, C=O, C=C, C–O, and C–C groups.